2019
DOI: 10.1111/1365-2435.13401
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic and terrestrial resources are not nutritionally reciprocal for consumers

Abstract: Aquatic and terrestrial ecosystems are connected through reciprocal fluxes of energy and nutrients that can subsidize consumers. Past research on reciprocal aquatic–terrestrial subsidies to consumers has generally focused on subsidy quantity while ignoring major differences in the nutritional composition of aquatic and terrestrial resources. Because aquatic resources contain substantially more highly unsaturated omega‐3 fatty acids (HUFAs) than terrestrial resources, aquatic subsidies may play a unique role by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(137 citation statements)
references
References 51 publications
3
128
0
Order By: Relevance
“…Rarely have spatial subsidies been placed in a geographic context but as ecologists are tasked with addressing problems at increasingly large spatial scales, knowing where cross-ecosystems linkages are most important could inform management interventions and study designs to better understand local ecosystem functions (Loreau et al 2003, Turner and Chapin 2005, McCluney et al 2014. For example, the Lower Mississippi (VPU08) hydrologic region is relatively well dissected by streams and has a high number of confluences and narrow subbasins.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely have spatial subsidies been placed in a geographic context but as ecologists are tasked with addressing problems at increasingly large spatial scales, knowing where cross-ecosystems linkages are most important could inform management interventions and study designs to better understand local ecosystem functions (Loreau et al 2003, Turner and Chapin 2005, McCluney et al 2014. For example, the Lower Mississippi (VPU08) hydrologic region is relatively well dissected by streams and has a high number of confluences and narrow subbasins.…”
Section: Discussionmentioning
confidence: 99%
“…Omega‐3 highly unsaturated fatty acids (HUFAs) are known to be highly important in consumer diets (Twining et al, ), and HUFAs have been shown to be more abundant in aquatic than terrestrial organisms (Hixson, Sharma, Kainz, Wacker, & Arts, ). Twining et al () analysed the relative abundance of the short‐chain precursor to HUFAs (ALA, alpha linolenic acid) versus HUFAs themselves within aquatic and terrestrial prey items, collected at three different study sites, and found that aquatic prey contained a much higher overall percentage of HUFAs, but not more ALA, compared to terrestrial prey. Thus, aquatic insect prey contained more HUFAs relative to terrestrial prey on a per capita basis at their study sites.…”
mentioning
confidence: 99%
“…It makes sense that fish would get more HUFAs from aquatic prey if the quantity of prey ingested were the only important factor. But compound‐specific stable isotope analyses of four different fatty acids showed that both stream fish and riparian bird chicks relied on aquatic insects for HUFAs in their diets (Twining et al ). This demonstrates that, irrespective of the aquatic prey contribution to their overall diet, HUFAs came predominantly from aquatic insect prey.…”
mentioning
confidence: 99%
See 2 more Smart Citations